Sarcoidosis: Progression to the chronic stage and pathogenic based treatment (narrative review) - Malkova, Anna; Zinchenko, Yulia; Starshinova, Anna; Kudlay, Dmitriy; Kudryavtsev, Igor; Glushkova, Anzhela; Yablonskiy, Piotr; Shoenfeld, Yehuda (Frontiers in Medicine, 2022)
Many factors confirm the autoimmune nature of sarcoidosis and help in determining the strategy of patient management and treatment initiation. However, the causes and the mechanisms of disease progression that result in fibrosis and insufficiency of the affected organ remain unclear. This narrative review aims to analyse the mechanisms and biomarkers of sarcoidosis progression, as well as the pathogenetic basis of sarcoidosis therapy. The following characteristics of progressive chronic sarcoidosis were revealed: the disease develops in patients with a genetic predisposition (SNP in genes GREM1, CARD15, TGF-β3, HLA-DQB1*06:.02, HLA-DRB1*07/14/15), which contributes either the decreased ability of antigen elimination or autoimmune inflammation. Various prognostic biomarkers of disease progression (decreased levels of neopterin, elastase, sIL-2R, chitotriosidase, glycoprotein Krebs von den Lungen, Th17 cell count, reduced quantity of TNF-α in peripheral blood or bronchoalveolar lavage fluid) have been described and can potentially be used to determine the group of patients who will benefit from the use of corticosteroids/cytostatic drugs/biologics.